System dynamics modeling in competitive cocoa agroindustry management: a case study of Socolatte in Pidie Jaya regency - Lukman Hakim; Agustina Arida; Fajri Fajri; Monalisa Monalisa; Cut Faradilla (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
The declining competitiveness of the regional cocoa agroindustry poses a major challenge to sustainably enhancing the added value of cocoa commodities. This study aims to design a competitive management model for the cocoa agroindustry in Pidie Jaya Regency, using Socolatte as a case study of a community-based processing industry. A system dynamics approach was used as the modeling method, based on systems thinking and incorporating feedback loops and time delays to understand complex behavioral dynamics within the agroindustry management system. Primary data were collected through in-depth interviews with key stakeholders across the cocoa value chain, including farmers, traders, processors, company leaders, and cooperatives. Secondary data were obtained from relevant institutions. The model was formulated and simulated using Vensim PLE software. The results identified ten key sub-models: cocoa bean transportation, harvesting on company/cooperative plantations, sales from supported smallholder farms, harvesting on independent smallholder farms, processing capacity management, factory labor, final processing stages, Socolatte inventory management, Socolatte market and order system, and Socolatte financial management. The novelty of this study lies in the holistic integration of various sub-systems within a community-based cocoa agroindustry into a single dynamic modeling framework, which has rarely been applied in a localized context such as Pidie Jaya. The model maps causal relationships across production, management, distribution, and financial aspects simultaneously, providing a strategic decision-making tool for agroindustry stakeholders. These findings offer strategic insights to improve system efficiency, enhance product value, and increase profitability for both smallholder cocoa farmers and local cocoa processing companies in Pidie Jaya Regency.